Ionic conductivity studies on magnesium-based cellulose acetate polymer gel electrolytes / Aniza Omar … [et al.] - Omar, Aniza; Zainal Abidin, Siti Zafirah; Kamisan, Ainnur Sherene; Saaid, Siti Irma Yuana; Ali, Ab Malik Marwan; Yahya, Muhd Zu Azhan (Institute of Research Management and Innovation (IRMI), 2015)
Magnesium-based polymer gel electrolytes consist of magnesium triflate (MgTf) salt, a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) solvents as well as cellulose acetate as a polymeric agent were prepared via direct dissolution method. The highest ionic conductivity obtained for MgTf-EC:DEC(l: 1) liquid electrolytes was 2.66 x 10~3 S cm1 and enhanced to 2.73 x 10~3 S cm1 with the addition of cellulose acetate. These results were in agreement with the activation energy obtained with the lowest value of 0.11. The best explanation on the enhancement in ionic conductivity ofPGE is due to the "breathingpolymeric chain model". The plots of conductivity-temperature were shown to obey an Arrhenius rule. The electrical properties of the sample with the highest conductivity were analyzed using electrical permittivity-based frequency and temperature dependence in the range of 100Hz- 1 MHz and303-373K, respectively. The variation in dielectric permittivity (er ande) as a function of frequency at different temperatures exhibited decays at higher frequencies and a dispersive behavior at low frequencies. Based on the observed electrical properties, it can be inferred that this polymer gel electrolyte could be a promising candidate as an electrolyte in electrochemical devices.